2014
DOI: 10.1378/chest.13-1900
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Pulmonary Hypertension in the Elderly

Abstract: BACKGROUND: Pulmonary hypertension (PH) is common in elderly patients, but a detailed analysis of the causes of PH in the elderly has not been performed. We hypothesized that pulmonary arterial hypertension (PAH) is rare in elderly patients and sought to describe the characteristics of these patients at a large referral center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 21 publications
1
39
3
2
Order By: Relevance
“…In another study focusing on African Americans, despite the similarity in age (56.1±12.6 years) and female predominance (67.5%) of the studied population, PH was more associated with obesity, diabetes mellitus, and obstructive or restrictive spirometry patterns . In addition, Pugh and colleagues reported that WHO groups 2 and 3 were most frequently diagnosed (28% and 17%, respectively) in elderly patients (>65 years) with PH . Therefore, when looking at any registry, differences need to be identified between the target population, the intended population, and the population actually studied.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study focusing on African Americans, despite the similarity in age (56.1±12.6 years) and female predominance (67.5%) of the studied population, PH was more associated with obesity, diabetes mellitus, and obstructive or restrictive spirometry patterns . In addition, Pugh and colleagues reported that WHO groups 2 and 3 were most frequently diagnosed (28% and 17%, respectively) in elderly patients (>65 years) with PH . Therefore, when looking at any registry, differences need to be identified between the target population, the intended population, and the population actually studied.…”
Section: Discussionmentioning
confidence: 98%
“…Choudhary and colleagues reported that the prevalence of PH in African Americans above 65 years of age was 10 times that of those younger than 45 years of age . The higher prevalence of PH in the elderly may be related to decreasing compliance of the pulmonary arteries with age . In addition, older male patients often have concomitant diseases, thereby resulting in worse outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…The age showed no statistical difference. In this study we tried to avoid old population for possible association with emphysematous lung changes [18,19]. Pulmonary hypertension can develop at any age according to underlining cause.…”
Section: Discussionmentioning
confidence: 99%
“…This finding deserves more attention. Studies have found that the most common type of PAH in the elderly is the type associated with left heart diseases, particularly left atrial or ventricular heart disease 4. Grigioni et al11 analyzed 196 cases of patients with class III–IV heart failure; after they adjusted for the clinical and laboratory examinations and other indicators, they found that PAH is an independent predictor of acute heart failure and cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…However, further research has found that the prevalence and mortality of PAH are on the rise in the elderly population 3,4. The pathogenesis of PAH is closely related to heart and pulmonary circulation.…”
Section: Introductionmentioning
confidence: 99%